Mobile Music Distribution: A Multichannel Approach. (28th September 2011) - Furini, Marco
Abstract : In contrast to what is happening in the Internet-based scenario, the music market in the mobile scenario is far from being considered a large success. Several studies state that excessive downloading time and high cost are the main burdens. Motivated by the growth of social and mobile applications, in this paper we propose an approach that aims at reducing both the downloading time and the cost to get digital music when acquired in the mobile scenario. The proposed architecture exploits the usage of personal communication technologies embedded in cellphones (e.g., Bluetooth and Wi-Fi) to couple the current distribution model (mainly based on 3G networks), so as to provide a multichannel distribution model where users are free to redistribute digital music. The architecture includes a license-based security mechanism that prevents unauthorized usage of digital music, and makes use of an incentive mechanism to stimulate and reward the music distribution among customers. By analyzing pros and cons of the music distribution chain, results show that the proposed architecture might help in reducing both the downloading time and the cost to get digital music when acquired in the mobile scenario. Therefore, it might be helpful to the success of the mobile music scenario.